Capnodis cariosa (Pallas, 1776) found in a new Romanian location at the northern limit of its distribution range (Coleoptera: Buprestidae) - Ruicanescu, Adrian; Dumbravă, Amalia-Raluca; Drăghici, Andreea-Cătălina (Fragmenta entomologica, 2022)
Here we report a new population of Capnodis cariosa from the South-Western Romania, at the border with the Republic of Serbia (Danube’s Defile). The presence of this species was reported in the past from Southern Dobroudja (South-Eastern Romania, near the Bulgarian border), this being its only, yet nowadays probably extinct, local Romanian population. In our citizen science-based investigations, which started in the spring of 2020, we found 16 specimens in the area of the Iron Gates Natural Park, between Dubova and Svinița (Danube’s Defile, Mehedinți County). This location represents the northernmost one for this species in Europe and the only verified present-day location for this species in Romania. Some considerations about biology, ecology and distribution of Capnodis cariosa are also provided. Two updated distribution maps of this species in Romania, in the Danube’s Defile and in the whole Mediterranean areas, are also presented.